Indoor Corridor and Office Propagation Measurements and Channel Models at 8, 9, 10 and 11 GHz - Iury Da Silva Batalha; Andrea V. R. Lopes; Jasmine P. L. Araujo; Bruno L. S. Castro; Fabricio J. B. Barros; Gervasio Protasio Dos Santos Cavalcante; Evaldo Goncalves Pelaes (IEEE Access, 2019)
Recent research into radio propagation and large-scale channel modeling shows that frequencies can be used above 6 GHz for the new generation of mobile communications (5G). This paper provides a detailed account of measurement campaigns that use directional horn antennas in co-polarization (V-V and H-H) and cross-polarization (V-H) in line-of-sight (LOS) and obstructed-line-of-sight situations between the transmitter and receptor; they were carried out in a corridor and computer laboratory located at the Federal University of Para (UFPA). The measurement data were used to adjust path loss prediction models of radio propagation, through the minimum mean square error (MMSE) method, for indoor environments in the frequencies of 8-11 GHz. The parameters for the models that were determined are as follows: path loss exponent, polarization exponent (co- and cross-polarization), effects of shadowing and path loss exponent for wall losses. Standard deviation and standard deviation point by point are included as statistical metrics. The approximations with regard to the large-scale path loss models for frequencies of 8-11 GHz show a convergence with the measured data, owing to the method employed for the optimization of the MMSE to determine the parameters of the model.